Políticas públicas : análise da formação da agenda pública de cultura em Roraima (2013 a 2018) - Levino, Selmar de Souza Almeida (2019)
This dissertation aims to analyze the process of formation of the public agenda of culture in Roraima and its dialogue with the National System of Culture (CNS) from 2013 to 2018. The research is justified by the academic and social relevance of the study to contribute to the collection of information about the social reality of Roraima in the theme of culture, the role of the actors and the responsibilities of the public power as mediator of the multiple demands for the achievement of cultural policy objectives. As for the methodology, the study is anchored in a qualitative approach, it gathers data found in documentary and bibliographic sources related to the research object. As a technique for collecting information, we used individual semi-structured interviews with people who contributed to the discussion and organization of the public agenda formation process during the analyzed period. The selection of interviewees covered segments of public power and civil society, observing the competencies, attributions and conditions of participation of each interviewee in the formation of the public agenda. As for the analysis variables, the Multiple Flows Model was used. The research was based on theoretical references that approach the concept and the main theoretical aspects of culture, public policies and cultural policies. Among the results achieved were: the identification of visible and invisible actors, the way a the-me is presented as a demand; the alternatives and solutions of cultural policies in the state scope; how the process of dialogue between government and civil society takes place; the stage of organization of the CNS in Roraima and how the public agenda welcomes actions aimed at promoting cultural diversity in the State. It was noted that the objectives of cultural diversity are not achieved, as foreseen in the national culture policy, and that the process of forming the public cultural agenda in Roraima is dynamic, with changes occurring very rapidly according to the political will of decision makers, that is, they can fluctuate and can obstruct or redefine the agenda when government actors change or when political priorities arise whose interests surpass the current agenda.